Hollow fiber gas separation membrane

By adopting the preparation method of hollow fiber gas separation membranes and using specific materials and processes, the deficiencies in separation performance and strength of the existing CO2/CH4 separation membranes are solved, and high-efficiency and strong gas separation effects are achieved, which is suitable for Separation and large-scale production of CO2/CH4 system.

CN119327280AActive Publication Date: 2025-01-21SHANDONG RONGXING MEMBRANE MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411890475.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-01-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing CO2/CH4 separation membranes have shortcomings in terms of separation performance and strength, and it is difficult to meet the needs of efficient separation.

Method used

The preparation method of a hollow fiber gas separation membrane is used to mix the single acetate glycerin and acetate with polyether, sulfine polyether, and polyethylene pyricone-K60 and other materials. Harmony is treated, forming a casting fluid and preparing a hollow fiber membrane through the spraying head, and eventually performs heat treatment and drying under specific conditions to obtain a gas separation membrane with excellent CO2/CH4 separation performance and high -intensity.

Benefits of technology

The efficient separation performance and high intensity of the CO2/CH4 separation membrane are implemented. It is suitable for the separation of the CO2/CH4 system. The preparation process is highly efficient and suitable for large -scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327280A_ABST
    Figure CN119327280A_ABST
Patent Text Reader

Abstract

The invention provides a hollow fiber gas separation membrane, and belongs to the technical field of membrane materials. According to the technical scheme, firstly, glyceryl monoacetate and isobutyl acetate are used for constructing a mixed solvent, the mixed solvent is mixed with polyethersulfone, sulfonated polyetheretherketone and a pore-foaming agent under the medium-temperature condition, then cooling is conducted step by step, polyvinyl alcohol and zirconium oxide powder are sequentially added, polyacrylamide is added after primary ball milling is conducted, ball milling is conducted again, a membrane casting solution system is obtained, and standing and defoaming are conducted for use; diethylene glycol and propylene carbonate are adopted as core liquid, a hollow fiber membrane blank is extruded by a hollow fiber membrane spinning machine, the hollow fiber membrane blank directly enters 90% glycerol to be subjected to coagulating bath, phase separation and curing are carried out, and then the hollow fiber gas separation membrane is obtained after medium-temperature cleaning and heat treatment. The carbon dioxide separation membrane has excellent carbon dioxide separation performance, the membrane strength is remarkably improved, and the carbon dioxide separation membrane is particularly suitable for separation of a CO2 / CH4 system. In addition, the preparation process disclosed by the invention has relatively high efficiency and is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of membrane materials, in particular to a hollow fiber gas separation membrane. Background Art

[0002] Biogas (BNG) is a new renewable clean energy that has emerged in recent years. The core of preparing biogas is to remove carbon dioxide from biogas. The separation methods of CO2 / CH4 system currently mainly include adsorption separation, cryogenic separation, and membrane separation. Among them, adsorption separation technology uses the difference in adsorption capacity of adsorbents for CO2 and CH4 to achieve separation. Commonly used adsorbents include zeolite molecular sieves, activated carbon, and metal organic framework (MOF) materials. The equipment required for this method is relatively simple and flexible to operate, and it is suitable for small and medium-scale applications; the disadvantage is that the energy consumption of adsorbent regeneration is high and needs to be replaced regularly. Cryogenic separation technology cools the mixed gas to an extremely low temperature, causing CO2 to condense at low temperature, thereby achieving separation. This method is suitable for occasions with high purity requirements, but it has high energy consumption and large equipment investment.

[0003] Membrane separation technology uses the difference in permeation rates of different gas molecules through membrane materials to achieve separation. CO2 / CH4 separation membrane technology is considered to be the most promising technology in the field of biogas purification. The selection and design of membrane materials have an important influence on the separation efficiency. Commonly used membrane materials include polymer membranes and inorganic membranes. The membrane biogas purification process includes gas purification, compression, cooling and drying steps, and finally high-purity biogas can be achieved. In recent years, some researchers have used polyether copolyamide (Pebax) as the separation layer membrane material and prepared composite gas separation membranes by dip coating. The permeation separation performance of Pebax composite membranes for pure gases such as CH4, CO2 and H2S and a series of CO2 / CH4 mixed gases was investigated. The cross-flow model of spiral wound membrane separator was used to simulate and analyze the technical feasibility of Pebax gas separation membranes for biogas purification. It was found that Pebax membranes have a certain CO2 permeation flux and CO2 / CH4 separation coefficient. In addition, some researchers used tetramethyl biphenol, dichlorodiphenyl sulfone and difluorobenzophenone as monomers to synthesize polyether sulfone through condensation, and then prepared amino-functionalized polyether sulfone gas separation membrane through bromination and amination, which improved the separation effect to a certain extent. However, the separation performance of the above separation membranes still has room for improvement, and there are generally problems such as low membrane strength and short service life. Summary of the invention

[0004] The technical problem to be solved by the present invention is: how to develop a gas separation membrane with better CO2 / CH4 separation performance and higher strength.

[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: A hollow fiber gas separation membrane is prepared by the following method: 1) Add monoacetin and isobutyl acetate to a stirring kettle, stir evenly at 40-60°C, add polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60, stir at 80-90°C for 1-2h, then cool to 50-60°C, add polyvinyl alcohol, cool to 30-40°C and keep warm, then add zirconium oxide powder, ball mill, then add polyacrylamide, ball mill, stir under negative pressure for 8-12h, transfer to a spinning kettle and let stand for degassing to obtain a casting solution; 2) Diethylene glycol and propylene carbonate are mixed to obtain a core liquid, the casting liquid is degassed and then added to the spinneret, the core liquid is injected into the inner insert of the spinneret, the casting liquid is squeezed into 90% glycerol at 5°C, solidified, then washed in an ethylene glycol environment at 50°C, and then heat-treated in dimethyl silicone oil at 130°C to obtain hollow fiber membrane fibers; 3) The hollow fiber membrane fibers are cleaned with deionized water, rinsed in a methanol environment at 55° C., and then cleaned with deionized water and dried to obtain the hollow fiber gas separation membrane.

[0006] Preferably, in step 1), the mass ratio of monoacetin to isobutyl acetate is 1:2-1:3.5.

[0007] Preferably, in step 1), the molar ratio of polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60 is 1:4:2.5.

[0008] Preferably, in step 1), the amount of zirconium oxide powder added is 1 / 8 to 1 / 15 of the mass of polyethersulfone, the rotation speed of the first ball milling is 300 rpm, and the rotation speed of the second ball milling is 550 rpm.

[0009] Preferably, the negative pressure state in step 1) is 0.2-0.35 atmospheres, the stirring time under the negative pressure state is 5-8 hours, and the temperature is 25-35°C.

[0010] Preferably, during the static degassing process in step 1), the system is placed in an ultrasonic oscillation environment, the static degassing time is 3-6 hours, and the temperature is 25-35°C.

[0011] Preferably, the ratio of polyethersulfone, sulfonated polyetheretherketone, polyvinylpyrrolidone-k60, polyvinyl alcohol, zirconium oxide powder, polyacrylamide, monoacetin, isobutyl acetate, glycol and propylene carbonate is 10g: 7.8g: 4.2g: 5.5g: 1.35g: 3.13g: 20mL: 13mL: 17mL: 5mL.

[0012] Preferably, in step 2), the water pressure entering the inner diameter of the spinning head is 1.8 bar and the water flow rate is 140 mL / min.

[0013] Preferably, in step 2), the residence time of the hollow fiber membrane embryo in 90% glycerol at 5° C. is not less than 40 minutes.

[0014] Preferably, the drying in step 3) is vacuum drying at a temperature of 40-50°C.

[0015] Preferably, in step 3), after the drying step is completed, the hollow fiber gas separation membrane is kept in a nitrogen and oxygen environment with a volume ratio of 1:1 for 20 to 30 minutes.

[0016] The present invention provides a hollow fiber gas separation membrane. The technical solution first constructs a mixed solvent with monoacetin and isobutyl acetate, mixes with polyethersulfone, sulfonated polyetheretherketone and porogen under medium temperature conditions, and then cools step by step and adds polyvinyl alcohol and zirconium oxide powder in sequence, adds polyacrylamide after one ball milling, and then ball mills to obtain a casting liquid system, which is then placed for degassing and used for standby; the core liquid uses diethylene glycol and propylene carbonate, and a hollow fiber membrane embryo is extruded using a hollow fiber membrane spinning machine, and directly enters 90% glycerol for coagulation bath to cause phase separation and solidification, and then obtains a hollow fiber gas separation membrane after medium temperature cleaning and heat treatment. The present invention has excellent carbon dioxide separation performance, and the membrane strength is significantly improved, and is particularly suitable for the separation of CO2 / CH4 systems. In addition, the preparation process of the present invention has high efficiency and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a scanning electron microscope image of the hollow fiber gas separation membrane of the present invention.

[0018] Figure 2 yes Figure 1 A partial enlarged view of . DETAILED DESCRIPTION

[0019] The specific embodiments of the present invention will be described in detail below. In order to avoid too much unnecessary details, the well-known structures or functions will not be described in detail in the following examples. The approximate language used in the following examples can be used for quantitative expression, indicating that the quantity can be allowed to have a certain change without changing the basic function. Unless otherwise defined, the technical and scientific terms used in the following examples have the same meaning as those generally understood by those skilled in the art to which the present invention belongs.

[0020] Example 1 A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 40°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60, stirring at 80°C for 1 hour, then cooling to 50°C, adding polyvinyl alcohol, cooling to 30°C for insulation, adding zirconium oxide powder, ball milling, adding polyacrylamide, ball milling, stirring under negative pressure for 8 hours, transferring to a spinning kettle for static degassing, and obtaining a casting solution; 2) adding diglycerol Alcohol and propylene carbonate are mixed to obtain a core liquid, and the casting liquid is degassed and added to the spinneret, and the core liquid is injected into the inner tube of the spinneret, and the casting liquid is squeezed into 90% glycerol at 5°C, solidified, and then washed in an ethylene glycol environment at 50°C, and then heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane; 3) The hollow fiber membrane is washed with deionized water, and then rinsed in a methanol environment at 55°C, and then the hollow fiber membrane is washed with deionized water and dried to obtain the hollow fiber gas separation membrane. For the obtained hollow fiber gas separation membrane, its breaking strength is detected to be 72MPa; the performance is tested using a mixed gas of CO2 and CH4 (volume ratio of 25:75). When the feed gas pressure is 0.13MPa, the CO2 permeation rate is 2100×10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 256.

[0021] Example 2 A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 60°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60, stirring at 90°C for 2h, then cooling to 60°C, adding polyvinyl alcohol, cooling to 40°C for insulation, adding zirconium oxide powder, ball milling, adding polyacrylamide, ball milling, stirring under negative pressure for 12h, transferring to a spinning kettle for static degassing, and obtaining a casting solution; 2) adding diglycerol Alcohol and propylene carbonate are mixed to obtain a core liquid. After the casting liquid is degassed, it is added to the spinneret, and the core liquid is injected into the inner tube of the spinneret. The casting liquid is squeezed into 90% glycerol at 5°C, solidified, and then washed in an ethylene glycol environment at 50°C, and then heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane; 3) The hollow fiber membrane is washed with deionized water, then rinsed in a methanol environment at 55°C, and then washed with deionized water, and dried to obtain the hollow fiber gas separation membrane. For the obtained hollow fiber gas separation membrane, its breaking strength is detected to be 77MPa; the performance is tested using a mixed gas of CO2 and CH4 (volume ratio of 30:70). When the feed gas pressure is 0.15MPa, the CO2 permeation rate is 2400×10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 280.

[0022] Example 3 A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 50°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60, stirring at 85°C for 1.5 hours, then cooling to 55°C, adding polyvinyl alcohol, cooling to 35°C for insulation, adding zirconium oxide powder, ball milling, adding polyacrylamide, ball milling, stirring under negative pressure for 10 hours, transferring to a spinning kettle for static degassing, and obtaining a casting solution; 2) adding two Glycol and propylene carbonate are mixed to obtain a core liquid. After the casting liquid is degassed, it is added to the spinneret, and the core liquid is injected into the inner tube of the spinneret. The casting liquid is squeezed into 90% glycerol at 5°C, solidified, and then cleaned in an ethylene glycol environment at 50°C, and then heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane; 3) The hollow fiber membrane is cleaned with deionized water, then rinsed in a methanol environment at 55°C, and then the hollow fiber membrane is cleaned with deionized water and dried to obtain the hollow fiber gas separation membrane. For the obtained hollow fiber gas separation membrane, its breaking strength is detected to be 69MPa; the performance is tested using a mixed gas of CO2 and CH4 (volume ratio of 25:75). When the feed gas pressure is 0.12MPa, the CO2 permeation rate is 1800×10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 221.

[0023] Example 4 A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 50°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60, stirring at 85°C for 1.5 hours, then cooling to 55°C, adding polyvinyl alcohol, cooling to 35°C for insulation, adding zirconium oxide powder, ball milling, adding polyacrylamide, ball milling, stirring under negative pressure for 10 hours, transferring to a spinning kettle for static degassing, and obtaining a casting solution; 2) adding two Glycol and propylene carbonate are mixed to obtain a core liquid, and the casting liquid is degassed and added to the spinneret, and the core liquid is injected into the inner tube of the spinneret, and the casting liquid is squeezed into 90% glycerol at 5°C, solidified, and then washed in an ethylene glycol environment at 50°C, and then heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane; 3) The hollow fiber membrane is washed with deionized water, and then rinsed in a methanol environment at 55°C, and then the hollow fiber membrane is washed with deionized water, and dried to obtain the hollow fiber gas separation membrane. The mass ratio of monoacetin to isobutyl acetate in step 1) is 1:3. The molar ratio of polyethersulfone, sulfonated polyetheretherketone, and polyvinylpyrrolidone-k60 in step 1) is 1:4:2.5. In step 1), the amount of zirconium oxide powder added is 1 / 10 of the mass of polyethersulfone, the speed of the first ball milling is 300rpm, and the speed of the second ball milling is 550rpm. The negative pressure state in step 1) is 0.3 atmospheres, the stirring time under negative pressure is 6h, and the temperature is 30°C. During the static degassing process in step 1), the system is in an ultrasonic oscillation environment, the static degassing time is 4h, and the temperature is 30°C. For the obtained hollow fiber gas separation membrane, its breaking strength was detected to be 85MPa; its performance was tested using a mixed gas of CO2 and CH4 (volume ratio of 30:70). When the feed gas pressure was 0.15MPa, the CO2 permeation rate was 2800×10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 297.

[0024] Example 5 A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 50°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60, stirring at 85°C for 1.5 hours, then cooling to 55°C, adding polyvinyl alcohol, cooling to 35°C for insulation, adding zirconium oxide powder, ball milling, adding polyacrylamide, ball milling, stirring under negative pressure for 10 hours, transferring to a spinning kettle for static degassing, and obtaining a casting solution; 2) adding two Glycol and propylene carbonate are mixed to obtain a core liquid, and the casting liquid is degassed and added to the spinneret, and the core liquid is injected into the inner tube of the spinneret, and the casting liquid is squeezed into 90% glycerol at 5°C, solidified, and then washed in an ethylene glycol environment at 50°C, and then heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane; 3) The hollow fiber membrane is washed with deionized water, and then rinsed in a methanol environment at 55°C, and then the hollow fiber membrane is washed with deionized water, and dried to obtain the hollow fiber gas separation membrane. The mass ratio of monoacetin to isobutyl acetate in step 1) is 1:3. The molar ratio of polyethersulfone, sulfonated polyetheretherketone, and polyvinylpyrrolidone-k60 in step 1) is 1:4:2.5. In step 1), the amount of zirconium oxide powder added is 1 / 10 of the mass of polyethersulfone, the speed of the first ball milling is 300rpm, and the speed of the second ball milling is 550rpm. The negative pressure state in step 1) is 0.3 atmospheres, the stirring market under the negative pressure state is 6h, and the temperature is 30°C. During the static degassing process in step 1), the system is in an ultrasonic oscillation environment, and the static degassing time is 4h and the temperature is 30°C. In step 2), the water pressure entering the inner diameter of the spinning head is 1.8bar and the water flow rate is 140mL / min. In step 2), the residence time of the hollow fiber membrane embryo in 90% glycerol at 5°C is 50min. For the obtained hollow fiber gas separation membrane, its breaking strength is detected to be 83MPa; the performance test is carried out using a mixed gas of CO2 and CH4 (volume ratio of 30:70). When the feed gas pressure is 0.13MPa, the CO2 permeation rate is 2500×10 -6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 312.

[0025] Example 6 A hollow fiber gas separation membrane is prepared by the following method: 1) adding monoacetin and isobutyl acetate to a stirring kettle, stirring evenly at 50°C, adding polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60, stirring at 85°C for 1.5 hours, then cooling to 55°C, adding polyvinyl alcohol, cooling to 35°C for insulation, adding zirconium oxide powder, ball milling, adding polyacrylamide, ball milling, stirring under negative pressure for 10 hours, transferring to a spinning kettle for static degassing, and obtaining a casting solution; 2) adding two Glycol and propylene carbonate are mixed to obtain a core liquid, and the casting liquid is degassed and added to the spinneret, and the core liquid is injected into the inner tube of the spinneret, and the casting liquid is squeezed into 90% glycerol at 5°C, solidified, and then washed in an ethylene glycol environment at 50°C, and then heat-treated in dimethyl silicone oil at 130°C to obtain a hollow fiber membrane; 3) The hollow fiber membrane is washed with deionized water, and then rinsed in a methanol environment at 55°C, and then the hollow fiber membrane is washed with deionized water, and dried to obtain the hollow fiber gas separation membrane. The mass ratio of monoacetin to isobutyl acetate in step 1) is 1:3. The molar ratio of polyethersulfone, sulfonated polyetheretherketone, and polyvinylpyrrolidone-k60 in step 1) is 1:4:2.5. In step 1), the amount of zirconium oxide powder added is 1 / 10 of the mass of polyethersulfone, the speed of the first ball milling is 300rpm, and the speed of the second ball milling is 550rpm. The negative pressure state in step 1) is 0.3 atmospheres, the stirring time under negative pressure is 6h, and the temperature is 30°C. During the static degassing process in step 1), the system is in an ultrasonic oscillation environment, and the static degassing time is 4h and the temperature is 30°C. In step 2), the water pressure into the inner diameter of the spinning head is 1.8bar and the water flow rate is 140mL / min. In step 2), the residence time of the hollow fiber membrane embryo in 90% glycerol at 5°C is 50min. The drying in step 3) is vacuum drying at a temperature of 46°C. In step 3), after completing the drying step, the hollow fiber gas separation membrane is kept in a nitrogen and oxygen environment with a volume ratio of 1:1 for 25min. The fracture strength of the obtained hollow fiber gas separation membrane was 91 MPa. The performance of the membrane was tested by using a mixture of CO2 and CH4 (volume ratio of 40:60). When the feed gas pressure was 0.18 MPa, the CO2 permeation rate was 3200×10 - 6 cm 3 (STP) cm -2 ·s -1 cmHg -1 , the CO2 / CH4 separation factor is 349.

[0026] The embodiments of the present invention are described in detail above, but the contents are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the scope of the present invention shall be included in the protection scope of the present invention.

Claims

1. A hollow fiber gas separation membrane, characterized in that: It is prepared by the following method: 1) Add monoacetin and isobutyl acetate to a stirring kettle, stir evenly at 40-60°C, add polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60, stir at 80-90°C for 1-2h, then cool to 50-60°C, add polyvinyl alcohol, cool to 30-40°C and keep warm, then add zirconium oxide powder, ball mill, then add polyacrylamide, ball mill, stir under negative pressure for 8-12h, transfer to a spinning kettle and let stand for degassing to obtain a casting solution; 2) Diethylene glycol and propylene carbonate are mixed to obtain a core liquid, the casting liquid is degassed and then added to the spinneret, the core liquid is injected into the inner insert of the spinneret, the casting liquid is squeezed into 90% glycerol at 5°C, solidified, then washed in an ethylene glycol environment at 50°C, and then heat-treated in dimethyl silicone oil at 130°C to obtain hollow fiber membrane fibers; 3) The hollow fiber membrane fibers are cleaned with deionized water, rinsed in a methanol environment at 55° C., and then cleaned with deionized water and dried to obtain the hollow fiber gas separation membrane.

2. A hollow fiber gas separation membrane according to claim 1, characterized in that: In step 1), the mass ratio of monoacetin to isobutyl acetate is 1:2-1:3.

5.

3. The hollow fiber gas separation membrane according to claim 1, characterized in that: In step 1), the molar ratio of polyethersulfone, sulfonated polyetheretherketone and polyvinylpyrrolidone-k60 is 1:4:2.

5.

4. The hollow fiber gas separation membrane according to claim 1, characterized in that: In step 1), the amount of zirconium oxide powder added is 1 / 8 to 1 / 15 of the mass of polyethersulfone, the rotation speed of the first ball milling is 300 rpm, and the rotation speed of the second ball milling is 550 rpm.

5. The hollow fiber gas separation membrane according to claim 1, characterized in that: The negative pressure state in step 1) is 0.2-0.35 atmospheres, the stirring period under the negative pressure state is 5-8 hours, and the temperature is 25-35°C.

6. The hollow fiber gas separation membrane according to claim 1, characterized in that: During the static degassing process in step 1), the system is placed in an ultrasonic oscillation environment, the static degassing time is 3-6 hours, and the temperature is 25-35°C.

7. The hollow fiber gas separation membrane according to claim 1, characterized in that: In step 2), the water pressure entering the inner diameter of the spinning head is 1.8 bar and the water flow rate is 140 mL / min.

8. The hollow fiber gas separation membrane according to claim 1, characterized in that: In step 2), the hollow fiber membrane embryo is kept in 90% glycerol at 5° C. for no less than 40 minutes.

9. The hollow fiber gas separation membrane according to claim 1, characterized in that: The drying in step 3) is vacuum drying at a temperature of 40-50°C.

10. The hollow fiber gas separation membrane according to claim 1, characterized in that: In step 3), after the drying step is completed, the hollow fiber gas separation membrane is kept in a nitrogen and oxygen environment with a volume ratio of 1:1 for 20 to 30 minutes.

Citation Information

Patent Citations

  • Membranes for separation

    CN104010718A

  • Preparation method of gas separation membrane

    CN106422801A

  • Stable facilitated transport membranes for olefin / paraffin separations

    CN108602029A

  • Hollow fiber humidifying film as well as preparation method and application thereof

    CN114377555A

  • Polyimides dope composition, preparation method of hollow fiber using the same and hollow fiber prepared therefrom

    US20090286078A1